Meaning en Anglais et en Français: Emily in Paris’ Language Switching through Socio-Semantic Study - Sita Devi N., I Gst. Ayu P. Jesika; Wedananta, Kadek Adyatna (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
This research aims to figure out the types of code-switching applied in the Emily in Paris Netflix Series comes along with finding the meaning underlies in the code-switching used in each utterance. The data of this research were taken from the transcription of Emily in Paris Netflix Series Season 4. The data were collected through documentation method with the note taking technique. Descriptive-qualitative method was used to analyze the data. The theory used to analyze the types of code-switching proposed by Appel and Muysken (2005) and the theory to analyze the types of meaning proposed by Leech (1981). From the findings and analysis, it is found that there are seven tag-switches, nine intra-sentential, and nine inter-sentential language-switching applied in the utterances from the series. Along with that, it is also found that the conceptual meaning implied in ten data, connotative meaning implied in one data, four data with social meaning, seven data with affective meaning, and one data in reflected meaning. There is no data found for the collocative and thematic meaning. Keywords: Language-Switching, Meaning, English and French, Socio-Semantic, Netflix Series